Internalization of National Values Through Scouting Activities for Students at MTs Negeri Parepare City - Muhammad Harvin; Hasmiah Herawaty; Muzakkir; Zurahmah; Kalsum (Jurnal Pendidikan Sosial Indonesia, 2026)
The This study examines the internalization of nationalism values through scouting activities among students at MTs Negeri Parepare City. A descriptive qualitative approach was employed, utilizing observation, interviews, and documentation. Data were analyzed using the interactive model of Miles and Huberman. Respondents included the principal, scoutmasters, and students actively participating in scouting programs. The findings reveal that nationalism values were internalized through three stages: value transformation (introduction of values through flag ceremonies, recitation of Tri Satya and Dasa Dharma, and narratives of national heroes); value transaction (students’ engagement in teamwork, community service, leadership, and social activities); and value transinternalization (the embodiment of values in disciplined behavior, patriotism, and social responsibility). The internalized values included unity and integrity, law obedience, respect for national heroes, independence, leadership, and environmental awareness. These results indicate that scouting serves as an effective experiential medium for fostering nationalism and character development in educational settings. Penelitian ini mengkaji internalisasi nilai-nilai nasionalisme melalui kegiatan kepramukaan pada siswa MTs Negeri Kota Parepare. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik observasi, wawancara, dan dokumentasi. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman. Informan penelitian meliputi kepala madrasah, pembina pramuka, dan siswa yang aktif dalam kegiatan kepramukaan. Hasil penelitian menunjukkan bahwa internalisasi nilai nasionalisme berlangsung melalui tiga tahap, yaitu transformasi nilai (penanaman nilai melalui upacara bendera, pembacaan Tri Satya dan Dasa Dharma, serta kisah pahlawan nasional); transaksi nilai (keterlibatan siswa dalam kerja sama kelompok, bakti sosial, kepemimpinan, dan kegiatan sosial); serta transinternalisasi nilai (terwujudnya perilaku disiplin, cinta tanah air, dan kepedulian sosial). Nilai nasionalisme yang berkembang meliputi persatuan, ketaatan hukum, penghargaan terhadap jasa pahlawan, kemandirian, kepemimpinan, serta kepedulian lingkungan. Kegiatan kepramukaan efektif sebagai media pengalaman langsung dalam pembentukan karakter nasionalisme di sekolah.